Drosophila melanogaster as a model to study innate immune memory - Arch, Marta; Vidal, Maria; Koiffman, Romina; Melkie, Solomon Tibebu; Cardona, Pere-Joan (Frontiers in Microbiology, 2022)
Over the last decades, research regarding innate immune responses has gained increasing importance. A growing body of evidence supports the notion that the innate arm of the immune system could show memory traits. Such traits are thought to be conserved throughout evolution and provide a survival advantage. Several models are available to study these mechanisms. Among them, we find the fruit fly, Drosophila melanogaster. This non-mammalian model has been widely used for innate immune research since it naturally lacks an adaptive response. Here, we aim to review the latest advances in the study of the memory mechanisms of the innate immune response using this animal model.